Proceedings of the 29th ACM International Conference on Multimedia 2021
DOI: 10.1145/3474085.3475497
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Graphic Layout Generation via Latent Optimization

Abstract: Figure 1: Overview of our Constrained Layout Generation via Latent Optimization (CLG-LO) framework. Given a pre-trained Generative Adversarial Network (GAN) for layout generation and user-specified constraints, CLG-LO explores the latent code to find a layout that satisfies the constraints. CLG-LO can reuse the same GAN for varying constraints without re-training.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Kikuchi et al proposed LayoutGAN++ [9] demonstrating an improvement in handling user-specific constraints by optimizing layout in latent space. It got rid of using wireframe images with respect to the findings that the rendering layer is unstable with a dataset of a limited size.…”
Section: Related Workmentioning
confidence: 99%
“…Kikuchi et al proposed LayoutGAN++ [9] demonstrating an improvement in handling user-specific constraints by optimizing layout in latent space. It got rid of using wireframe images with respect to the findings that the rendering layer is unstable with a dataset of a limited size.…”
Section: Related Workmentioning
confidence: 99%
“…Model In addition, we do not choose a wire-frame discriminator like [Li et al, 2019] because we empirically found that this relation discriminator with transformers performs better, the same as [Kikuchi et al, 2021].…”
Section: Composition-aware Layout Discriminatormentioning
confidence: 99%
“…As deep learning develops, LayoutGAN [Li et al, 2019], LayoutVAE [Jyothi et al, 2019] and VTN [Arroyo et al, 2021] appear to produce layouts from noise. Meanwhile, some conditional layout generation methods have been proposed [Li et al, 2021;Lee et al, 2020;Kikuchi et al, 2021]. But all these methods concentrate on…”
Section: Related Workmentioning
confidence: 99%
“…And the overall loss is the weighted sum of L adv and L rec . In addition, we do not choose a wire-frame discriminator like [Li et al, 2019] because we empirically found this relation discriminator with transformers performs better, the same as [Kikuchi et al, 2021].…”
Section: Composition-aware Layout Discriminatormentioning
confidence: 99%